Grãos secos de destilaria com solúveis com alto teor de proteína na alimentação de codornas de corte - Slva, Brena Cristine Rosário (2020)
Expenses with food stand out as the factor with the greatest impact on quail production costs. In times of increase in the price of commercialization of the main inputs, it is common to search for alternative foods that can provide lower production costs. Among the alternative foods, the co-products of corn ethanol production are promising substitutes for protein ingredients, such as soybean meal. High protein distillers dried grains with solubles (HP-DDGS) are co-products of ethanol production, produced by removing fibers prior to fermentation. HP-DDGS has a high content of crude protein and crude energy, good levels of amino acids and, therefore, can be included in greater amounts in the diet of quails without impairing performance. In this sense, the objective was to determine the nutritional value of HP-DDGS for male and female meattype quails (Coturnix coturnix coturnix; Experiment I), and to evaluate the effects of including HP-DDGS in the meat-type quail diet on performance yield, carcass and cut yield, meat quality, organ morphometry and economic analysis (Experiment II). In Experiment I, 96 meat-type quails were distributed in a randomized block design, in a 2x2 factorial arrangement (two diets and two genders), with six replicates and four quails per experimental unit, using the total excreta collection method. The experimental diets consisted of a reference-diet and a test-diet with isometric replacement of 200 g/kg of the reference-diet by HP-DDGS. In Experiment II, 612 meat-type quails were distributed in a completely randomized design with six inclusions levels of HP-DDGS (0, 85, 170, 255, 340 or 425 g / kg) in order to replace the soybean meal of the diets. At 42 days of age, the carcass and cuts yield, organ morphometry and meat quality were evaluated. The metabolism coefficient of crude protein was higher for males (747,53 g / kg) than for females (722,84 g/kg). The HP-DDGS EMAn content for males and females was 12,51 and 12,29 MJ/kg, respectively. The increase in HP-DDGS levels in the diet quadratically affected body weight (P = 0,020) and weight gain (P = 0,019) in the period from one to 21 days of age, with estimates of 296,02 and 296,22 g / kg of HP-DDGS for maximum body weight and weight gain for meat-type quails. The increase in HP-DDGS levels in substitution of soybean meal in the diet did not affect slaughter weight and weight gain, carcass and cut yield, meat quality, morphometry of the organs of cutting quails at 42 days of age and economic analysis. It is concluded that the HP-DDGS EMAn value for male and female meat-type quails is 12,40 MJ/kg. HP-DDGS can totally replace soybean meal without affecting meat performance, yield and quality and organ morphometry.